The Effect of Internal Marketing Orientation on Nurses' performance with the Mediating Role of Nurses' Engagement - Mehrdad Estiri; Mitra Rezvani; Abbas Nargesian (Tehran University of Medical Sciences, 2021)
Background: The performance of nurses as the largest human resources element of health care organizations has an important impact on the quality and results of patients' treatment. The main purpose of this research is to investigate the impact of internal marketing orientation on nurses' performance by considering the mediating role of nurses' engagement. Materials & Methods: In this regard, while reviewing the implications of internal marketing orientation, engagement with the job and performance of employees, using path analysis and structural equation modeling, we examined the effect of internal marketing orientation on the performance of nurses by examining the role of mediation in job engagement. The study population included nurses of Sasan and Parsian hospitals in Tehran. Stratified random sampling and a questionnaire were used to collect the data. In order to analyze the data, Kolmogorov-Smirnov tests were used for the normal test and Path Analysis and Structural Equation Modeling for confirmation of hypotheses. Results: Results showed that internal marketing orientation, through the engagement of nurses, influences their performance. Moreover, it was proved that internal marketing orientation has a direct relationship with engagement, but it does not directly influence nurses' performance. Conclusion: The most significant achievement of this research is that the managers and executives of healthcare centers can provide a more suitable environment for nurses caring patients, through improving working conditions. Implementing internal marketing orientation is one of the practices that can enhance nurses' performance through affecting work attitudes, especially work engagement.